Charge Storage: Transition from Diffusion‐Controlled Intercalation into Extrinsically Pseudocapacitive Charge Storage of MoS2 by Nanoscale Heterostructuring (Adv. Energy Mater. 1/2016). Issue 1 (January 2016) - Mahmood, Qasim; Park, Sul Ki; Kwon, Kideok D.; Chang, Sung‐Jin; Hong, Jin‐Yong; Shen, Guozhen; Jung, Young Mee; Park, Tae Jung; Khang, Sung Woon; Kim, Woo Sik; Kong, Jing; Park, Ho Seok
Abstract : In article number 1501115, Ho Seok Park and co‐workers demonstrate the transition of layered dichalcogenides from a diffusion‐controlled intercalation into extrinsically pseudocapacitive charge storage by downscaling into nanometric sheets. The resulting nanosheets are hybridized with electronically conductive reduced graphene oxide. The unique surface‐dominant phenomena originating from the strong interplay and heterostructure of the heteronanosheets is associated with the outstanding capacitive performances.